KKN SISDAMAS: Pendampingan Program Digitalisasi Branding UMKM Opak Singkong Lokal Danantya - Anggia, Tazkia; Candrayani, Rosida; Maulana, Irham; Rizky, Alvin muhammad; Tajiri, Hajir (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
The Opak Singkong Danantya MSME, located in Wargamekar Village, faces significant challenges in terms of product legality, branding, and marketing. This study aims to improve the competitiveness of MSMEs through a mentoring program that includes obtaining a Home Industry Food Production Certificate (SPPIRT), improving branding with a more attractive logo and label design, and registering products on e-commerce platforms such as Shopee. The methods used include analyzing MSME needs, implementing necessary changes, and training to utilize digital technology. The results of this activity indicate that MSMEs can overcome existing obstacles and significantly expand their market reach. In conclusion, this mentoring has succeeded in providing a strong foundation for MSME development by utilizing technology and effective branding. The implications of the results of this study are the need for ongoing support for MSMEs to maintain growth and competitiveness in a competitive market, as well as the potential use of this model for other MSMEs with similar challenges.